Morbidity and mortality of patients with haemophilia in Germany 2007/2008 - Krebs, H.; Spannagl, M.; Schramm, W.; für die teilnehmenden Behandlungseinrichtungen (Hämostaseologie, 2009)
Since 1978 an annual multicentric survey regarding the epidemiology of patients suffering of haemophilia is performed with support of haemophilia treating centres of any size. Again the actual compilation is resting upon a broad database returning to over 30 years of inquiry well representing both the actual and retrospective status of mortality. Prompted was exclusively information about patients with haemophilia A, B and von Willebrand disease. In particular anonymous data concerning the last 12 months about number of treated patients, type and severity of illness, HIV-status and detailed information about causes of death was inquired. This data was merged with existing data and analyzed statistically. In the 2007/2008 survey, a total
Keywords: Haemophilia; haemophilia A; haemophilia B; von Willebrand disease; epidemiology; factor VIII; factor IX; morbidity; mortality; cause of death; HIV; AIDS; HCV